Effects of a non‐absorbing substrate on the magneto‐optical Kerr response of plasmonic ferromagnetic nanodisks. Issue 5 (17th April 2014) - Maccaferri, Nicolò; Kataja, Mikko; Bonanni, Valentina; Bonetti, Stefano; Pirzadeh, Zhaleh; Dmitriev, Alexandre; van Dijken, Sebastiaan; Åkerman, Johan; Vavassori, Paolo
<x xml:space="preserve">Abstract</x> Magnetoplasmonics is an emerging field of intense research on materials combining magnetic and plasmonic functionalities. The novel optical and magneto‐optical (MO) properties displayed by these materials could allow the design of a new class of magnetically controllable optical nano‐devices. In this work, we investigate the effects of a non‐absorbing (insulating) substrate on the MO activity of pure ferromagnetic disk‐shaped nanostructures supporting localized plasmon resonances. We show that the red‐shift of the localized plasmon resonance, related to the modification of the localization of the electromagnetic field due to the substrate, is not the only effect that the substrate has on the MO response. We demonstrate that the reflectivity of the substrate itself plays a key role in determining the MO response of the system. We discuss why it is so and provide a description of the modeling tools suitable to take into account both effects. Understanding the role of the substrate will permit a more aware design of magnetoplasmonic nanostructured devices for future biotechnological and optoelectronic applications. <inline-graphic xlink:href="ark:/27927/pgh27gw89m" content-type="pssa201300701-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Ferromagnetic nickel nanodisk in vacuum (left) and on a non‐absorbing substrate (right), illuminated by linearly polarized light. The polarization of the reflected field is changed in the first case due to a combination of intrinsic magneto‐optical properties and the nanoconfinement of the material. In the second case, the polarization of the reflected light is affected also by the presence of the substrate.